Occurrence and molecular characterization of Potato spindle tuber viroid (PSTVd) isolates from potato plants in North China - Cai-ling QIU; Zhi-xiang ZHANG; Shi-fang LI; Yan-ju BAI; Shang-wu LIU; Guo-quan FAN; Yan-ling GAO; Wei ZHANG; Shu ZHANG; Wen-he LÜ; Dian-qiu LÜ (Journal of Integrative Agriculture, 2016)
Abstract: China is the largest potato producing country worldwide, with this crop representing the fourth largest staple food crop in China. However, the steady presence of Potato spindle tuber viroid (PSTVd) over the past five decades has a significant economic impact on potato production. To determine why PSTVd control measures have been ineffective in China, more than 1 000 seed potatoes collected between 2009 and 2014 were subjected to PSTVd detection at the Supervision and Testing Center for Virus-free Seed Potatoes Quality, Ministry of Agriculture, China. A high PSTVd infection rate (6.5%) was detected among these commercial seed potatoes. Some breeding lines of potato collected from 2012 to 2015 were also tested for PSTVd infection, revealing a high rate of PSTVd contamination in these potato propagation materials. Furthermore, comparison of the full-length sequences of 71 different Chinese PSTVd isolates revealed a total of 74 predominant PSTVd variants, which represented 42 different sequence variants of PSTVd. Comparative sequence analysis revealed 30 novel PSTVd sequence variants specific to China. Comprehensive phylogenetic analysis uncovered a close relationship between the Chinese PSTVd sequence variants and those isolated from Russia. It is worth noting that three intermediate strains and six mild strains were identified among these variants. These results have important implications for explaining the ineffective control of PSTVd in China and thus could serve as a basic reference for designing more effective measures to eliminate PSTVd from China in the future.